Antjie Krog: Poetry Is The Answer! - Douman, Bronwyn (WritingThreeSixty: Journal or Research and Creative Text, 2018)
WritingThreeSixty sat down with esteemed author and academic, Professor Antjie Krog, on Thursday 4 June 2015, in her office at the University of the Western Cape.